A Semiotic Analysis on Robert Frost’s Poem Love and a Question Based on Charles Sander Peirce’s Triangle Theory - Anita Candra Dewi; Asrifan, Andi (MultiTech Publisher, 2023)
This research aims to identify Robert Frost's symbols in